Common variants on 9p21.3 are associated with brain arteriovenous malformations with accompanying arterial aneurysms - Bendjilali, Nasrine (2014)
OBJECTIVE: To investigate whether previously reported 9p21.3 single nucleotide polymorphisms (SNPs) are associated with risk of brain arteriovenous malformations (BAVMs), which often have accompanying arterial aneurysms. Common variants in the 9p21.3 locus have been reported to be associated with multiple cardiovascular phenotypes, including coronary artery disease and intracranial aneurysms (rs10757278 and rs1333040). METHODS: We used data from 338 BAVM cases participating in the University of California, San Francisco-Kaiser Brain AVM Study Project and 504 healthy controls to evaluate genotypes for seven common SNPs (minor allele frequency>0.05) that were imputed using 1000 Genomes Phase 1 European data (R(2)>0.87). Association with BAVM was tested using logistic regression adjusting for age, sex and the top three principal components of ancestry. Subgroup analysis included 205 BAVM cases with aneurysm data: (a) 74 BAVM with aneurysm vs. 504 controls, and (b) 131 BAVM without aneurysm vs. 504 controls. RESULTS: We observed suggestive association with BAVM and rs10757278-G (OR=1.23, 95% CI=0.99–1.53, P=0.064) and rs1333040-T (OR=1.27, 95% CI=1.01–1.58, P=0.04). For rs10757278-G, the association was stronger in BAVM cases with aneurysm (OR=1.52, 95% CI=1.03–2.22, P=0.032) than in BAVM without aneurysm (OR=0.98, 95% CI=0.72–1.34, P=0.91). Similar patterns of effects were observed for rs1333040 and for other SNPs in linkage disequilibrium (r(2)>0.8) with rs10757278. CONCLUSIONS: Common 9p21.3 variants showed similar effect sizes for association with BAVM as previously reported for aneurysmal disease. The association with BAVM appears to be explained by known associations with aneurysms, suggesting that BAVM associated aneurysms share similar vascular pathology mechanisms with other aneurysm types.